2020
DOI: 10.3390/ani10061041
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and In Vitro Evaluation of Fenugreek (Trigonella foenum-graecum) Seed Gum as a Potential Prebiotic in Growing Rabbit Nutrition

Abstract: Some components of soluble fibre appear to have prebiotic effects that can contribute to improving digestive health in post-weaning rabbits. In this work, a fenugreek seed gum (FGS), extracted from Trigonella foenum-graecum seeds and rich in galactomannan, was characterised. Both the pure FSG and ten substrates obtained by the inclusion of 0, 5, 10, 15 and 20 g/kg of FSG in diets rich in soluble (SF) and insoluble (IF) fibre were evaluated in vitro to determine FSG prebiotic potential for rabbit diets. FSG was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Microencapsulation of Lactiplantibacillus plantarum 15HN in a gel formulation (1.5% alginate with 0.5% fenugreek) provided adequate bacterial cell viability under low pH and high bile salt concentrations [160]. In a study by Zemzmi et al on the effect of mucilage on rabbits, fermentation by cecal bacteria was observed and the gel was resistant to digestive enzymes in vitro, indicating the potential prebiotic effect of fenugreek seed gel extract [161].…”
Section: Trigonella Foenum-graecummentioning
confidence: 99%
“…Microencapsulation of Lactiplantibacillus plantarum 15HN in a gel formulation (1.5% alginate with 0.5% fenugreek) provided adequate bacterial cell viability under low pH and high bile salt concentrations [160]. In a study by Zemzmi et al on the effect of mucilage on rabbits, fermentation by cecal bacteria was observed and the gel was resistant to digestive enzymes in vitro, indicating the potential prebiotic effect of fenugreek seed gel extract [161].…”
Section: Trigonella Foenum-graecummentioning
confidence: 99%
“…Gum possesses diverse properties of attracting water giving them high viscosity and swelling properties and its ability to form a biofilm ( Mohammadinejad et al, 2020 ). The application of gum-derived seed was studied in the gastrointestinal tract through drug release ( Zemzmi et al, 2020 ), and on colorectal cancer as antitumor medications ( Chaurasia et al, 2006 ).…”
Section: Plant Seed Extracts As Potential Source For Biomedical Scaff...mentioning
confidence: 99%
“…Moreover, the limitation on the prophylactic use of antibiotics in animal production produced in Europe in the last years led to an increase in rabbit mortality in many farms, often making production almost economically unsustainable [7,8]. In this respect, the main challenge in rabbit production is to maintain gut health in the rabbits during the post-weaning period [9][10][11], when the digestive tract is very vulnerable and susceptible to the proliferation of bacterial pathogens (e.g., Clostridium perfringens and Escherichia coli) and parasitic protozoa (e.g., coccidians) [12]. In this context, alternatives to antibiotics that improve the gut health and resilience of rabbits to pathogens are required [6], and dietary strategies are especially key in the post-weaning period [13,14].…”
Section: Introductionmentioning
confidence: 99%